Agricultural Output and Economic Growth: Evidence from Nigeria - Samuel, Afolabi Olusesan Samuel (African Journal of Stability and Development (AJSD), 2025)
This study examines the effect of agricultural output on economic growth in Nigeria between 1981 and 2021. The main objective of the study is to examine the impact of crop production, livestock production, fishery and forestry on economic growth in Nigeria. The type of data necessary for this study is secondary because the research work is analytical in nature. Time series data relating to the dependent and explanatory variables were employed for a period covering 1981 and 2021. Data used in this study were sourced through Central Bank of Nigeria (CBN) Statistical Bulletin, Federal Bureau of Statistics (FBS), and World Bank Data Base (WBDB). The variables examined had varying results. Crop Production, Livestock Production and Fishery production exhibited positive correlation on Gross Domestic Product (GDP), whereas a divergent nexus was found for Forestry. Moreover, when the level of value of agricultural output declines, it mitigates against the growth of an emerging economy like Nigeria. It is hereby recommended that to improve agriculture, the government should see that special incentives are given to farmers. These should include: adequate funding and infrastructure such as good roads, pipe-borne water, and electricity. Moreover, the government should discourage people from the act of bush burning, especially during the dry season, in order to preserve the trees in the forest.